That's not my fire engine ... : its doors are too bumpy - Watt, Fiona; Wells, Rachel; Figg, Non (London : Usborne Publishing Ltd, London, 2023)
Turn the pages to discover the fire engines with their bumpy doors, squashy wheels and sparkly lights as they speed through the pages of this sturdy board book. Babies and toddlers will love exploring the different tactile patches, as well as spotting the familiar little white mouse
On board pages with textured inserts.
Preschool.
Keywords: Readers; Fire engines -- Juvenile fiction; Picture books for children; Board books